Implementasi Permainan Dengan Media Informasi Dan Teknologi (IT) dalam Mengembangkan Sosial Emosional Anak Kelompok B Di TK Pertiwi Randu, Boyolali Tahun Ajaran 2015/2016 - Hasanah, Eka Uswatun; , Dra. Surtikanti, S.H.,M.Pd (2016)
Emotional social abilities of early childhood social emotional needs to be developed as an early ability for children to interact with their environment more broadly. The education process has now shifted with the times that used to only use books and other woods, the technology is now utilized for the benefit of improved services and quality of education. This study aimed to obtain data on the implementation of the game with the media and information technology in developing children's social emotional group B at TK Pertiwi Randu. In the preparation of this paper takes two data. First, the theoretical data is obtained from a number of books dealing with the problems examined. Second, the empirical data obtained through jump directly to the object of research by using observation, interview and documentation. From the research we concluded that game with tenologi media and social information can develop an emotional child in training self-esteem, respect for others, willing to ask and answer questions, following the rules, patiently waiting their turn, and the train never give up attitude.